Analysis of Job Satisfaction as an Intervening Variable in The Relationship Between Compensation, Transformational Leadership, and Workload Towards Turnover Intention of Contract Nurses at Hospital X - Ria Permata; Ratna Indrawati; Rina Mutiara (Management Dynamics: International Journal of Management and Digital Sciences, 2026)
There is one problem related with source Power man that is turnover that occurred at Hospital X and is known reach more from 10%. Research aiming for analyze Job Satisfaction as an intervention in connection between compensation compensation, leadership transformational, and burden Work to turnover intention in nurses power Work contract at Hospital X. Research use approach quantitative with type explanatory. Population in study is all over Labor Nurse Contract at Hospital as many as 562 people. The sampling method used is non-probability sampling. Research data This using primary data that is done with share questionnaire in a way direct through google form with alternative answer use scale Likert. Research This use approach Structural Equation Model (SEM) with measurement model using Smart PLS program version 3.2.9. Research results This find that in a way simultaneous all over variable influential to turnover intention. In partial compensation, leadership transformational, and burden Work found own influence significant to Job Satisfaction. More carry on in a way partial satisfaction too work, compensation, leadership transformational, and burden Work own influence significant to turnover intention.